Impacto de polimorfismos genéticos do doador e do receptor sobre a ocorrência de função retardada do enxerto renal - Primo Junior, Amador Goncalves [UNIFESP] (2016)
Objective: The aim of the present study was to investigate association between single nucleotide polymorphisms (SNPs) in donors (D) and recipients (R) of kidney allografts and occurrence of delayed graft function (DGF), defined as the need for dialysis in the first week after transplantation (Tx). Methods: Twenty-eight candidate genes were selected from an extensive and rigorous literature review: ATF3, BAX, BCL2, CLCN6, CX3CL1, CXCL1, CXCL10, EDN1, EPAS1, FABP1, GSTP1, HAVCR1, HMOX1, ICAM1, IL8, JAG1, LGALS3, MCPH1, NGAL, NOS2, PARP1, SELP, SHROOM3, SPATA5L1, STC1, TLR4, UMOD and VEGF. The candidate SNP, in each of these genes, was selected using a prioritization tool (SNPLogic - www.snplogic.org). Two cohorts of Tx with kidney from deceased donors and adult recipients, both from predominantly Caucasian ancestry were analyzed in the study. The exploratory cohort included 579 Tx performed between January 2007 and February 2012 (in 217 Tx we studied both D and R, in 249 Tx, only the R, and in 94 Tx, only the D. The validation cohort, included 400 Tx, performed between February 2012 and October 2014 and in all cases we were able to studied both R and D. The DNA was obtained from buffy coat of peripheral blood and TaqMan® OpenArray? Genotyping System (Thermo Fisher Scientific Inc., Waltham, MA, EUA) was used to genotype 29 SNPs in 28 genes. Statistics included Fisher's exact and Mann-Whitney tests or T tests, and multiple regression analyses. Significance was set at p<0.05. Results: DGF prevalence was 51.1% in the exploratory cohort, and 63.7% in the validation cohort. In the exploratory cohort, only the SNP rs2146323, in VEGFA of donors (p=0.0004, OR=2.310, 95%CI=1.465-3.643) and the SNP rs1871042, in GSTP1 of recipients (p=0.0066, OR=1.680, 95%CI=1.159-2.435) were associated with DGF. A multiple regression analysis including both SNPs and donor?s terminal serum creatinine ? 1.5 mg/dL (p=0.0005, OR=1.544, 95% CI=1.304-1.829), revealed that the three variables were independently associated with the outcome. In the validation cohort, however, only the association of donor?s terminal serum creatinine ? 1.5 mg/dL and DGF persisted. Conclusion: we conclude that this robust study, including 979 Tx and a total of 885 recipients and 730 donors, did not provide evidence of association of any of the 29 investigated SNPs with DGF. We speculate that the absence of, or difficulty to uncover, association between SNPs and DGF could be ascribed to the major impact of environmental factors in the pathogenesis of DGF, like, as shown in the present study, the terminal renal function of the donor.